2022
DOI: 10.1002/kin.21616
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the curing kinetics of polyurethane/nitrocellulose blends through FT‐IR measurements

Abstract: Polyester (HTPS) based polyurethane (PU) elastomers were currently established to be effective binders for high-energy composites with improved performances. Conventional PU binders are mostly non-energetic materials, and consequently reduce the energy performance significantly. Nitrocellulose (NC), is an energetic polymer widely used as an ingredient in propellants, explosives, fireworks, and gas generators, it may be introduced in PU-based compositions to overcome their performance drawback. Kinetic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…The urethane group can be seen through the FT‐IR spectra analysis in Figure 9, and it proved that PUEs have indeed been successfully prepared. The absorption peak at 1725 cm −1 is due to the asymmetric stretching vibration of CO 39,48 . The absorption peak at 3350 cm −1 is attributed to the NH stretching vibration and the tiny peak at 1575 cm −1 is caused by the NH bending vibration 49 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The urethane group can be seen through the FT‐IR spectra analysis in Figure 9, and it proved that PUEs have indeed been successfully prepared. The absorption peak at 1725 cm −1 is due to the asymmetric stretching vibration of CO 39,48 . The absorption peak at 3350 cm −1 is attributed to the NH stretching vibration and the tiny peak at 1575 cm −1 is caused by the NH bending vibration 49 .…”
Section: Resultsmentioning
confidence: 97%
“…The absorption peak at 1725 cm À1 is due to the asymmetric stretching vibration of C O. 39,48 The absorption peak at 3350 cm À1 is attributed to the N H stretching vibration and the tiny peak at 1575 cm À1 is caused by the N H bending vibration. 49 The absorption peak at 1370 cm À1 is due to the stretching vibration of C N. 50,51 In addition, there are slight differences between two types of PUEs, one PUEs are prepared with the participation of the alcoholysis products and the another are prepared directly with original polyester diols.…”
Section: The Characterization Of the Prepared Puesmentioning
confidence: 99%
“…It was used as a highly effective explosive in military and industrial applications and is also used as a binder in some solid rocket propellants. [78][79][80][81] NC is produced by the nitration of cellulose, a natural polymer found in plants, using nitrating agents such as sulfuric and nitric acids. 82 NC is a solid binder with a high-energy content, making it effective as a fuel for rocket propulsion.…”
Section: Gap/nc Copolymer Bindermentioning
confidence: 99%
“…The curing kinetics of PU and PU/NC blend systems were also analyzed using FTIR. 104 The activation energy and the curing kinetic model were determined. The results showed that in the case of PU systems, the addition of excess isocyanate groups had a significant autocatalytic effect.…”
Section: Nc Based Copolymer Bindermentioning
confidence: 99%
See 1 more Smart Citation